Recent Developments in Photofunctional Nanomaterials and Nanostructures for Emitting, Manipulating, and Harvesting Light - Zhixing Gan (Nanomaterials, 2024)
Photofunctional nanomaterials and nanostructures that can emit, manipulate, convert, and utilize photons in diverse forms have profound meanings, from fundamental understandings to applications [...]